2015
DOI: 10.1186/s12957-015-0643-1
|View full text |Cite
|
Sign up to set email alerts
|

The role of lymph nodes in predicting the prognosis of ampullary carcinoma after curative resection

Abstract: BackgroundLymph node involvement is one of the well-demonstrated prognostic factors in ampullary carcinoma. The aim of this study is to clarify the role of lymph nodes in predicting the survival outcome of ampullary carcinoma.MethodsA cohort of consecutive curative pancreaticoduodenectomies for ampullary carcinoma from 1999 to 2014 was retrospectively analyzed. The effect of node-associated variables, including lymph node status, positive lymph node number, total harvested lymph node (THLN) number, and lymph n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 39 publications
1
12
0
1
Order By: Relevance
“…Although the 8th edition of the AJCC guidelines redefines the grouping of RNP and confirms its impact on prognosis,4 our study showed that LNR greatly impacts the nomogram, whereas the effect of the number of RNP is excluded from the Cox multivariate analysis. The result indicates that LNR plays an important role in prognosis assessment of ampullary carcinoma, a fact that has been demonstrated in other studies 1618. LNR is incorporated into two variables—RNP and RNE; it not only considers the impact of RNP but also the impact of the total number of RNE on prognosis.…”
Section: Discussionsupporting
confidence: 63%
“…Although the 8th edition of the AJCC guidelines redefines the grouping of RNP and confirms its impact on prognosis,4 our study showed that LNR greatly impacts the nomogram, whereas the effect of the number of RNP is excluded from the Cox multivariate analysis. The result indicates that LNR plays an important role in prognosis assessment of ampullary carcinoma, a fact that has been demonstrated in other studies 1618. LNR is incorporated into two variables—RNP and RNE; it not only considers the impact of RNP but also the impact of the total number of RNE on prognosis.…”
Section: Discussionsupporting
confidence: 63%
“…Ampulla kanserlerinde, literatürde tümör boyutu, tümörün derecesi, evre, lenf nodu metastazı varlığı prognoza etkili faktörler arasında belirtilmektedir [18]. Ampulla kanserlerinde lenf nodu metastazı izlenme yüzdesi %30-50 arasında değişmektedir [19,20]. Ampuller adenokarsinomların prognozu, PDA'ya oranla daha iyi olup, 5 yıllık yaşam süresi %30-60 olarak bildirilmektedir [20].…”
Section: Resim 10 Periampuller Tümörlerinde Izlenen Prognoz Dağılım Yüzdesiunclassified
“…Recently, a retrospective study enrolled 111 patients who underwent Whipple surgery found that patients with ≥3 local LNMs had similar survival time as compared with the patients with distant LNM ( 1 ). Moreover, the total number of harvested lymph nodes is also a vital prognostic factor in AC ( 8 , 12 , 15 , 17 ). In view of this, some studies evaluated node staging for AC based on lymph node ratio (LNR) ( 7 , 9 , 11 , 18 , 23 ).…”
Section: Introductionmentioning
confidence: 99%